PEMIKIRAN MUSDAH MULIA TENTANG KEPEMIMPINAN POLITIK PEREMPUAN - Hendri Saputra (Pascasarjana UIN Fatmawati Sukarno Bengkulu, 2016)
Abstract: Speaking role of women in the public sphere, as if it never finishes. This is because the role of women in the public sphere, especially political role believed to be less significant. Until well into the third millennium, there are some scholars and intellectuals who view the role of negative and positive contribution of women in the political sphere. They do a textual interpretation of the Koran and the hadith which prohibits women involved in politics. Through constructive criticism and holistic reconstruction, this study attempts to explore the political role of women in public space idea Musdah Mulia. For Musdah, the thing to do is not only the reconstruction of the interpretation of the fundamental doctrines of Islam (al-Quran and Hadith), but also a practical movement in the field of education, culture, and public policy. All the reconstruction of the political leadership role of women should be carried out simultaneously in order to produce concrete changes. This is because there are a number of internal factors that cause women can not have a significant role in the political sphere that includes the figure of a woman’s own diffident and passive to the opportunities that exist. They also lack support, chained stereotypes as the guardian of the domestic sphere, remained shut misogynistic tradition, as well as the interpretation of religious bias patriarchal values and gender bias. In this study the authors use historical methods-qualitative and descriptive-analytic ie library research (library research) by studying, describing and analyzing the writings Musdah Mulia either in the form of books like any research, and writings that discuss ideas Musdah Mulia on women’s leadership, as well as other books that are relevant to the topic penulisbahas. The results showed that in view Musdah Mulia women can play a role in any sphere, including the public domain. In the political domain, women can play an active role in politics, ranging from the general election, active in a political party or participate in the realm of legislative, executive and judicial. The basis of such thinking is a) There is no difference in men and women. b) The essence of Islam is to humanize human beings and respect for sovereignty. c) The essence of religious teachings is to humanize humans, respect of human and glorify it. No matter what race, ethnicity, color, gender and social status. In fact, no matter what their religion; d) There is no prohibition in Islam related to women’s leadership in politics, even history records many women who play an active role both in the prophet and his companions at the time.